PREPARATION OF A WILL BY A NOTARY REGARDING MEDICAL DECISIONS REGARDING THE HEALTH OF A PATIENT WITH A TERMINAL ILLNESS - Islam, Syamsul; Budi Parnomo; Rahmatul Hidayati (International Journal of Cultural and Social Science, 2026)
Notarial practice in the health sector shows a new development when terminally ill patients document their medical wishes in a will before a notary. This phenomenon raises questions regarding the limits of a notary's authority and the validity of the patient's will in conditions of physical and psychological decline. This study uses a normative legal method with a statutory and conceptual approach. The results indicate that a terminally ill patient's will is most appropriately drafted in the form of a general will in accordance with Articles 875 and 938–940 of the Civil Code and Article 15 of the Notary Law. The testator's legal capacity is based on Articles 895, 1320, and 1330 of the Civil Code, while medical capacity is determined through the principle of informed consent as stipulated in the Medical Practice Law and the Health Law. If formal and material requirements are not met, the will has the potential to be invalidated or lose its authenticity, and it also creates professional responsibilities for the notary. These findings emphasize the need for specific guidelines to ensure legal certainty and protect the will of terminally ill patients.